2021
DOI: 10.1002/jcop.22720
|View full text |Cite
|
Sign up to set email alerts
|

PROJECT STAR (Midwestern Prevention Project): Overview

Abstract: The program designed to prevent substance use should be planned in multiple dimensions. One of these programs is Project Star. This study aims to evaluate the studies on the Project Star and identify the strengths and weaknesses of the program. For this purpose, the keywords “Project Star” and “Midwestern Prevention Project” were scanned from databases. The results of these studies were evaluated by giving a summary of the studies included in the study. As a result, the strengths of Project Star are that it is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 60 publications
0
1
0
Order By: Relevance
“…In addition, teachers can act as a protective factor for students, and thus it is recommended that the risk of substance abuse among youth who volunteer in emergency services after school hours is well-known to the school staff, and they should be provided with tools and special programs as to how to identify emotional distress and anxiety in their students to prevent substance abuse (Tesler et al, 2016). These tailored interventions may be based on prior effective drug prevention programs such as Project STAR, which focuses on strengthening students' ecological environment by helping them communicate, manage stress levels, and adjust their emotions (Göçmen et al, 2022). Another important review of international programs fighting against drugs showed that an efficient drug prevention program should focus on improving life skills, interactions, and increasing students' emotional awareness (Göçmen et al, 2021).…”
Section: Notementioning
confidence: 99%
“…In addition, teachers can act as a protective factor for students, and thus it is recommended that the risk of substance abuse among youth who volunteer in emergency services after school hours is well-known to the school staff, and they should be provided with tools and special programs as to how to identify emotional distress and anxiety in their students to prevent substance abuse (Tesler et al, 2016). These tailored interventions may be based on prior effective drug prevention programs such as Project STAR, which focuses on strengthening students' ecological environment by helping them communicate, manage stress levels, and adjust their emotions (Göçmen et al, 2022). Another important review of international programs fighting against drugs showed that an efficient drug prevention program should focus on improving life skills, interactions, and increasing students' emotional awareness (Göçmen et al, 2021).…”
Section: Notementioning
confidence: 99%